Single electron interference and capacitive edge mode coupling generates ϕ 0/2 flux periodicity in Fabry-Pérot interferometers - Shuang Liang; James Nakamura; Geoffrey Charles Gardner; Michael James Manfra (Nature Communications)
Abstract Experimental observations of flux periodicity ϕ 0/2, where ϕ 0 = h/e, for interference of the outermost edge mode in the integer quantum Hall regime have been attributed to an exotic electron pairing mechanism. We present measurements of an AlGaAs/GaAs Fabry-Pérot interferometer operated in the integer quantum Hall regime for filling factors 1 ≤ ν ≤ 3 that has been designed to simultaneously express measurable bulk-edge and edge–edge couplings. At integer fillings ν = 2 and ν = 3, we observe interference with flux periodicity ϕ 0/2 for the outermost edge mode. Our analysis indicates that the periodicity ϕ 0/2 is not driven by electron pairing but is the result of capacitive coupling between isolated edge modes and the interfering outer edge. The interfering unit of charge for the outermost edge mode at ν = 2 and ν = 3 was determined to be e * = 1, where the effective charge e * is normalized to the charge of an electron. Our measurements demonstrate that the magnitude of the interfering charge can be determined in operando in a Fabry-Pérot interferometer.